Canadian Public Health Laboratory Network Laboratory Guidelines for Congenital Syphilis and Syphilis Screening in Pregnant Women in Canada - Ameeta E Singh; Paul N Levett; Kevin Fonseca; Gayatri C Jayaraman; Bonita E Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
Despite universal access to screening for syphilis in all pregnant women in Canada, cases of congenital syphilis have been reported in recent years in areas experiencing a resurgence of infectious syphilis in heterosexual partnerships. Antenatal screening in the first trimester continues to be important and should be repeated at 28 to 32 weeks and again at delivery in women at high risk of acquiring syphilis. The diagnosis of congenital syphilis is complex and is based on a combination of maternal history and clinical and laboratory criteria in both mother and infant. Serologic tests for syphilis remain important in the diagnosis of congenital syphilis and are complicated by the passive transfer of maternal antibodies which can affect the interpretation of reactive serologic tests in the infant. All infants born to mothers with reactive syphilis tests should have nontreponemal tests (NTT) and treponemal tests (TT) performed in parallel with the mother’s tests. A fourfold or higher titre in the NTT in the infant at delivery is strongly suggestive of congenital infection but the absence of a fourfold or greater NTT titre does not exclude congenital infection. IgM tests for syphilis are not currently available in Canada and are not recommended due to poor performance. Other evaluation in the newborn infant may include long bone radiographs and cerebrospinal fluid tests but all suspect cases should be managed in conjunction with sexually transmitted infection and/or pediatric experts.